2014
DOI: 10.2147/ccid.s46051
|View full text |Cite
|
Sign up to set email alerts
|

Improving adherence to acne treatment: the emerging role of application software

Abstract: ObjectiveTo examine recent studies on the effect of mobile and electronic (ME)-health technology on adherence to acne treatment.BackgroundWith emerging use of ME-health technology, there is a growing interest in evaluating the effectiveness of the tools on medication adherence. Examples of ME-health technology-based tools include text message-based pill reminders and Web-based patient education.MethodsMEDLINE, Cochrane Library, and Web of Science were searched for articles on adherence to acne treatment publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Most studies on the topical treatment of acne have focused on adherence to therapy, the reasons for adherence, and suggested solutions. 311 This study revealed that discontinuation occurred mostly with the use of retinoids (40%), benzoyl peroxide combinations (44.1%), and retinoid combinations (60%). Furthermore, the reasons for discontinuation of these treatments were reported as a result of side effects, with rates of 50%, 33.3%, and 65.7%, respectively.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Most studies on the topical treatment of acne have focused on adherence to therapy, the reasons for adherence, and suggested solutions. 311 This study revealed that discontinuation occurred mostly with the use of retinoids (40%), benzoyl peroxide combinations (44.1%), and retinoid combinations (60%). Furthermore, the reasons for discontinuation of these treatments were reported as a result of side effects, with rates of 50%, 33.3%, and 65.7%, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…These findings indicate that side effects and unresponsiveness are the main reasons for discontinuation of topical treatment in patients with acne. A literature review by Park et al 5 revealed that adherence was higher among patients with acne taking oral medication than in those using topical medication.…”
Section: Discussionmentioning
confidence: 99%
“…Snyder et al stated that a physician’s ability to convey information about the medication is critical for treatment success and patient satisfaction [ 9 ]. For effective patient education and counselling on the treatment of chronic disease, various means of information such as reading materials, videos, and reminders may be utilized [ 21 – 23 ]. Recent studies have shown that written counselling significantly improved adherence in acne patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Young people are nowadays on average more engaged with technology and the internet than previous generations ( 5 ). This familiarity can positively influence the satisfaction of adolescent patients with teledermatology, since for most of these patients the correct handling of smartphones and telemedicine programs does not involve a big learning effort ( 5 , 8 ). Furthermore, such teledermatological check-ups might save patients’ time and avoid absences either at school or at work ( 5 , 9 ).…”
Section: Discussionmentioning
confidence: 99%